2013
DOI: 10.1083/jcb.201309038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of centrioles causes chromosomal instability in vertebrate somatic cells

Abstract: Centrosomes establish a mitotic spindle geometry that facilitates correct kinetochore–microtubule attachments, contributing to the fidelity of chromosome segregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
107
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 53 publications
18
107
0
Order By: Relevance
“…Many studies have correlated centrosomal aberrations with abnormal spindles and chromosomal instability (17,(40)(41)(42). Staining for α-tubulin in Sas4 −/− p53 −/− MEFs showed that bipolar spindles formed in the absence of SAS4 (Fig.…”
Section: Sas4-nullmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies have correlated centrosomal aberrations with abnormal spindles and chromosomal instability (17,(40)(41)(42). Staining for α-tubulin in Sas4 −/− p53 −/− MEFs showed that bipolar spindles formed in the absence of SAS4 (Fig.…”
Section: Sas4-nullmentioning
confidence: 92%
“…Abnormal numbers of centrioles are associated with cancer, although it is not clear whether abnormal centrosome number is a cause or an effect of tumorigenesis (1,(11)(12)(13). Studies in cultured cell lines have given conflicting results on the roles of vertebrate centrioles in mitosis, chromosome segregation, DNA damage response, and intercellular signaling (14)(15)(16)(17)(18)(19), but the precise functions of mammalian centrioles have not been defined genetically.…”
mentioning
confidence: 99%
“…Loss of centrosome integrity in cultured cells has been reported to induce senescence or p38 mitogen-activated protein kinase-dependent G1 arrest but whether these occur in cells with MCPH mutations remains to be seen [48][49][50]. Cells with abnormal centrosome numbers take longer to form a bipolar spindle and consequently show a mitotic delay [51][52][53][54][55]. In fact, mitotic delay is the major phenotype seen after depletion of WDR62, ASPM and STIL in developing zebrafish retinal neuroepithelium [56].…”
Section: Centrosomes In Brain Developmentmentioning
confidence: 99%
“…Cells containing too few or too many centrosomes exhibit transient anastral, mono-or multipolar spindles and frequent chromosome missegregation [53,61,62]. Chromosomal instability generates aneuploidy, which has a strong anti-proliferative effect owing to imbalanced gene expression [63].…”
Section: Centrosomes In Brain Developmentmentioning
confidence: 99%
“…We now know that these pathways normally act in concert to enhance the timeliness and fidelity of spindle assembly in animal cells. Indeed, when centrioles are not present in animal somatic cells, the fidelity of bipolar spindle assembly and fidelity of chromosome distribution in anaphase are significantly compromised [49,50].…”
Section: Centrioles Versus Centrosomesmentioning
confidence: 99%